Cost of Privacy-preserving SMPC Protocols for NN-Based Inference - Anonymous, A

Alfred Anderschs "Die Rote" mit Antonioni gelesen - Öhlschläger, Claudia (Das Italien des Alfred Andersch. Interkulturelle und intermediale Konstellationen)

Lattice Revocation Mechanisms - Lohse, Jan

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Exploring the effects of physics explainer videos and written explanations on declarative knowledge and the illusion of understanding - Kulgemeyer, Christoph; Hörnlein, Madeleine; Sterzing, Fabian (International Journal of Science Education)
Keywords: Education

Wie können Erklärvideos zum Erwerb physikalischen Konzeptwissens beitragen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

Democracy ≠ Democracy. Creating digital infographics to compare different democratic systems. - Janzen, Thomas (Englisch betrifft uns)

Geschlechtsidentität - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Sexuelle Orientierung - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Qualifizierung von Studierenden des Grund- und Förderschullehramts für Inklusion in Schule und Unterricht - Franzen, Katja; Albers, Timm; Hellmich, Frank (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Primary School Principals’ Views on the Required Conditions for a Successful Implementation of Inclusive Education - Görel, Gamze; Hellmich, Frank (Australasian Journal of Special and Inclusive Education)
Abstract Following the United Nations Convention on the Rights of Persons With Disabilities, questions concerning the joint education of students with and without special educational needs remain to be answered. Currently, there is a need for knowledge about the necessary conditions for a successful implementation of inclusive education. Thus, the aim of the present study is to identify conditions for the implementation of inclusion that are seen as necessary by primary school principals. Therefore, 32 primary school principals were interviewed. The results of the interview study reveal that factors like personnel, financial and material resources as well as building infrastructure in primary schools are seen as important requirements for the successful realisation of inclusive education. Apart from that, the importance of attitudes towards inclusion and sociopolitical conditions for the realisation of inclusion became apparent. Further conditions, which are mentioned from the interviewed principals’ point of view, are related to teacher training, appropriate class sizes and, for example, opportunities for exchanging information. The results of the study indicate that there are essential obstacles as perceived by primary school principals that can impede the implementation of inclusion in primary schools.
Keywords: General Engineering

Qualität der Erfahrungen aus dem inklusiven Unterricht und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

Adaptiver Unterricht in der (inklusiven) Grundschule aus der Perspektive von Lehrkräften - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

FRIEND-SHIP Intervention Program – The Handbook - Aroni, Katerina; Toulia, Anastasia; Alves, Sílvia Regina Gonçalves; Hassani, Sepideh; Heidrich, Franziska Anna; Franzen, Katja; Görel, Gamze; Löper, Marwin Felix; Aguiar, Teresa; Silveira-Maia, Mónica; Sanches-Ferreira, Maria Manuela Pires Sanches; Hellmich, Frank; et al.

Schlussbericht: Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) Entwicklung und Evaluation eines interdisziplinären Fortbildungsangebots - Lütje-Klose, Birgit; Wild, Elke; Gorges, Julia; Neumann, Phillip; Grüter, Sandra; Weber, Antonia

Der Rollenhut als Vermittlungsmedium - Rollenklärungsprozesse im Kontext multiprofessioneller Kooperationen als Thema universitärer Aus- und Fortbildungen von Lehrkräften und Sozialpädagog*innen - Neumann, Phillip; Hopmann, Benedikt; Lütje-Klose, Birgit (Herausforderung Lehrer*innenbildung - Zeitschrift zur Konzeption, Gestaltung und Diskussion)
Multiprofessionelle Kooperation zwischen allgemeinen und sonderpädagogischen Lehrkräften und mit weiteren Fachkräften, u.a. der Schulsozialarbeit, der Schulpsychologie und mit Schulbegleitungen, gilt bei der Entwicklung inklusiver Schulen als zentrale Stellschraube. Dementsprechend wird Kooperation im Kontext Schule auch in der universitären Ausbildung von zukünftig miteinander kooperierenden Professionen sowie in Fortbildungen für Lehrkräfte und multiprofessionelle Teams verstärkt ins Blickfeld gerückt. Zugleich lässt sich beobachten, dass in inklusiven Schulen bislang vermeintlich klare Zuständigkeiten, insbesondere zwischen Sonder- und Sozialpädagog*innen, aufweichen und neu austariert werden müssen. Bei der Entwicklung multiprofessioneller Teams gilt die Klärung von Rollen und Aufgaben als eine besondere Herausforderung, wenn unterschiedliche Professionen mit unterschiedlichen institutionellen Anbindungen und pädagogischen Zielperspektiven oder Grundhaltungen mitei-nander kooperieren. Das vorgestellte Instrument – der Rollenhut – dient dazu, in multiprofessionellen Gruppen eine individuelle Reflexion über die eigenen Aufgaben anzustoßen und auf dieser Grundlage gemeinsam über die gegenseitigen Erwartungen und Rollen zu diskutieren. Das Instrument wurde im Kontext von Fortbildungen multiprofessioneller Teams an Schulen konzipiert und auch im Rahmen der universitären Lehrer*innenbildung erprobt.

Teachers Between a Rock and a Hard Place: Goal Conflicts Affect Teaching Motivation Mediated by Basic Need Satisfaction - Gorges, Julia; Neumann, Phillip; Störtländer, Jan Christoph (Frontiers in Psychology)
Teaching is a highly demanding profession that requires handling multiple and potentially contradictory goals. Therefore, it is likely that teachers experience conflict between work-related goals on a daily basis. Intraindividual goal conflict may occur when individuals pursue multiple goals drawing on the same limited resources (resource-based goal conflict), or when two or more goals are incompatible in terms of goal attainment strategy or desired end states (inherent goal conflict). Because goal conflict is typically associated with negative effects such as attenuated motivation and wellbeing, teacher goal conflict may jeopardize teaching motivation. This cross-sectional study investigated the effects of in-service teachers’ ( N = 302) goal conflicts on their autonomous (intrinsic and identified regulation) and controlled (introjected and extrinsic regulation) teaching motivation and tested the satisfaction of teachers’ basic need for autonomy, competence, and relatedness as mediators. In line with our hypotheses, results from structural equation modeling showed that frequently experiencing resource-based goal conflict leads to a lower satisfaction of the basic need for autonomy, which, however, was unrelated to teaching motivation. In contrast, frequently experiencing inherent goal conflict attenuates the satisfaction of the basic need for competence, which, in turn, positively predicted autonomous teaching motivation and negatively predicted extrinsic regulation. As expected, relatedness was not associated with the experience of goal conflict. The discussion focuses on differential effects of the two types of goal conflict on teaching motivation and on the relevance to expand research on teachers’ intraindividual goal conflicts.
Keywords: General Psychology

Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) : Technical Report V. 1.0 - Gorges, Julia; Neumann, Phillip; Wild, Elke; Lütje-Klose, Birgit; Grüter, Sandra; Weber, Antonia; Senior, Jonathan

Reconfigurable and real-time high-bandwidth Nyquist signal detection with low-bandwidth in silicon photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Meier, Janosch; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Optics Express)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain detection of a high-bandwidth Nyquist signal with a low-bandwidth silicon photonics Mach-Zehnder modulator based receiver. As the Nyquist signal has a rectangular bandwidth, it can be multiplexed in the wavelength domain without any guardband as a part of a Nyquist-WDM superchannel. These superchannels can be additionally multiplexed in space and polarization. Thus, the presented demonstration can open a new possibility for the detection of multidimensional parallel data signals with silicon photonics. No external pulse source is needed for the receiver, and frequency-time coherence is used to sample the incoming Nyquist signal with orthogonal sinc-shaped Nyquist pulse sequences. All parameters are completely tunable in the electrical domain. The feasibility of the scheme is demonstrated through a proof-of-concept experiment over the entire C-band (1530 nm–1560 nm), employing a 24 Gbaud Nyquist QPSK signal due to experimental constraints on the transmitter side electronics. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can process Nyquist signals of 90 GHz optical bandwidth, suggesting a possibility to detect symbol rates up to 90 GBd in an integrated Nyquist receiver.

Flexible Time-Domain De-Multiplexing of Nyquist OTDM Channels by Orthogonal Sampling in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Conference on Lasers and Electro-Optics)
We report for the first time, inter-symbol-interference (ISI) free demultiplexing of Nyquist optical time division multiplexed (OTDM) signals using a reconfigurable orthogonal sinc-pulse sampling enabled by silicon photonic Mach-Zehnder Modulators.

Analysis of the effect of jitter and non-idealities on photonic digital-to-analog converters based on Nyquist pulses - Singh, Karanveer; Kress, Christian; Mandalawi, Younus; Misra, Arijit; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Emulation of integrated high-bandwidth photonic AWG using low-speed electronics - Singh, Karanveer; Meier, Janosch; Kress, Christian; Misra, Arijit; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Development of a crash behaviour prediction method for resistance spot welded 3-steel sheet joints - Olfert, Viktoria; Meschut, Gerson; Hein, David; Schuster, Lilia; Sommer, Silke
The recent trend towards extensive electric mobility leads to a variety of new challenges for the engineering of future vehicle concepts. One particular challenge is the additional weight added to the vehicle by the battery, which stands in direct contrast to the existing customer expectation of a high driving range. The reduction of the total vehicle weight is driven by the extensive use of ultra-high-strength steels in thin sheet thicknesses in car body construction. Resistance spot welding is the dominant joining process in steel-intensive lightweight construction due to its high degree of automation, process reliability and the associated economic efficiency. In order to comply limitations of the space in the vehicle body and to ensure the most efficient use of materials in lightweight construction, joints are used that connect several sheets with a single spot weld. This leads to new challenges for the prediction of the load-bearing capacity and failure behaviour under crash loading. This paper presents a systematic characterisation of 3 sheet steel joints in order to find formulary, empirical relationships between the load-bearing capacity of the joint and the affecting parameters. Numerical simulations are carried out in order to clarify the causes of occurring phenomena in experiments. For this purpose, influencing variables such as joint strength, joint arrangement, sheet thickness, sheet strength, load type and load case on the load bearing capacity and failure behaviour are identified. Furthermore, the extent to which the behaviour of 2-sheet joints can be transferred to 3-sheet joints is investigated. A formulary correlation enables a quick and inexpensive estimates of the load-bearing capacity of 3-sheet metal connections. These models can be used for a computer-efficient simulation of components with three layered spot welded joints.

Wideband SiN pulse interleaver for optically-enabled analog-to-digital conversion: a device-to-system analysis with cyclic equalization - Zazzi, Andrea; Müller, Juliana; Ghannam, Ibrahim; Battermann, Moritz; Rajeswari, Gayatri Vasudevan; Weizel, Maxim; Scheytt, J. Christoph; Witzens, Jeremy (Optics Express)
We present the design and experimental characterization of a silicon nitride pulse interleaver based on coupled resonator optical waveguide filters. In order to achieve a targeted free spectral range of 1.44 THz, which is large given the reduced optical confinement of the silicon nitride platform, individual ring resonators are designed with tapered waveguides. Its application to time-interleaved photonically-assisted ADCs is analyzed by combining experimental characterization of the photonic integrated circuit with a comprehensive model of the entire ADC. The impact of fundamental signal distortion and noise sources affecting the converter is investigated and suitable equalization techniques at the digital signal processing level are evaluated. The novel application of a simple but powerful equalization filter in the DSP domain allows for a significant improvement of the digitized signal SNR. An ENOB of 5 over a 75 GHz bandwidth (150 GS/s) and an ENOB of 4.3 over a 100 GHz bandwidth (200 GS/s) are expected to be achievable with compact and off-the-shelf single-section semiconductor mode locked lasers, that can be further improved with lower noise light sources.

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara

Die Bedeutung von Ressourcen für Lebensqualität und gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Lebensführung und Umgang mit Diversität– Haushaltswissenschaftliche Perspektiven - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Die Organisation der Daseinsvorsorge für die private Lebensführung reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lehren gestalten – Lernen ermöglichen. Fachdidaktische Hinweise - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lebensweise, Lebensführung und Lebensstile reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung zwischen Wissenschaft und Lebenswelt - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Konsumentscheidungen für die Lebensführung analysieren und reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung und Funktion des Rechts für die Lebensführung verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

'Women’s work is never easy, never clean': (Strong) Black Womanhood and the Carceral State in Tayari Jones’s An American Marriage - Hartmann, Alexandra (U.S. American Culture as Popular Culture)

Nothing Ever Ends: Critical Race Theory, Schwarzer Humanismus und Watchmen - Hartmann, Alexandra (Alle Uns: Differenz, Identität, Repräsentation)

Validation of the student version of the Perceptions of Inclusion Questionnaire in primary and secondary education settings - Knickenberg, Margarita; Zurbriggen, Carmen L. A.; Schwab, Susanne (SAGE Open)
Considering students’ voices and perspectives is indispensable in educational contexts. Therefore, instruments of measurement that are reliable and valid and can be used easily without complications are needed in schools. The Perceptions of Inclusion Questionnaire (PIQ) is a short instrument used to assess three central dimensions of inclusion, namely emotional and social inclusion and academic self-concept. Previous evaluations indicate in general high psychometric properties. This study aimed to evaluate the construct validity of the three scales of the PIQ’s student version using different approaches in two samples from primary (grade 4, N = 721) and secondary (grade 7, N = 393) schools. The results of confirmatory factorial analyses confirmed the PIQ’s three factors in both samples which are also measurement equivalent across grades. Plausible correlations with additional divergent and convergent scales reveal that the PIQ measures the theoretically assumed constructs—emotional and social inclusion as well as academic self-concept—validly.
Keywords: General Social Sciences; General Arts and Humanities

Recht und Wirtschaft in Europa, Bd. 1: Lüke: Reverse Factoring - Eine rechtliche und ökonomische Analyse - Krimphove, Dieter

Internationale Schiedgerichtsbarkeit: Perspektiven für die Wirtschaft - Krimphove, Dieter

MaRisk: Kommentar: Rundschreiben 10/2021 (BA) - Mindestanforderung an das Risikomanagement - Krimphove, Dieter; Lüke, Christoph

Völkerrecht und IPR - Krimphove, Dieter; Lentner, Gabriel

Kapitalmarktrecht - Krimphove, Dieter; Lüke, Christoph

Brave New Kachel-World? Über Zoom-Booming, Datenkontrolle und öffentliche Infrastrukturen - Weber, Jutta (Von Menschen und Maschinen – Mensch-Maschine-Interaktionen in digitalen Kulturen)

Ende des werberechtlichen Schattendaseins der "Hörmarke" - Zugleich eine Analyse von EuG "Ardagh Metal Beverage/EUIPO" - Krimphove, Dieter (Zeitschrift für Gewerblichen Rechtsschutz und Urheberrecht)

Die Körordnung im deutschen und Europäischen Recht - Krimphove, Dieter; Schlief, Till (Natur und Recht NuR)